# elyou=el

## Simple and best practice solution for elyou=el equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for elyou=el equation:

Simplifying
elyou = el
Solving
elouy = el
Solving for variable 'e'.
Move all terms containing e to the left, all other terms to the right.
Add '-1el' to each side of the equation.
-1el + elouy = el + -1el
Combine like terms: el + -1el = 0
-1el + elouy = 0
Factor out the Greatest Common Factor (GCF), 'el'.
el(-1 + ouy) = 0
Subproblem 1Set the factor 'el' equal to zero and attempt to solve:
Simplifying
el = 0
Solving
el = 0
Move all terms containing e to the left, all other terms to the right.
Simplifying
el = 0
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(-1 + ouy)' equal to zero and attempt to solve:
Simplifying
-1 + ouy = 0
Solving
-1 + ouy = 0
Move all terms containing e to the left, all other terms to the right.
Add '1' to each side of the equation.
-1 + 1 + ouy = 0 + 1
Combine like terms: -1 + 1 = 0
0 + ouy = 0 + 1
ouy = 0 + 1
Combine like terms: 0 + 1 = 1
ouy = 1
Add '-1ouy' to each side of the equation.
ouy + -1ouy = 1 + -1ouy
Combine like terms: ouy + -1ouy = 0
0 = 1 + -1ouy
Simplifying
0 = 1 + -1ouy
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.`